Short‐term effects in a reduced flow stretch: The case of the Antas River in South Brazil. (13th March 2019) - Borba, Cristina S.; Latini, João D.; Baumgartner, Matheus T.; Gomes, Luiz C.; Agostinho, Angelo A.
Abstract: The building of adduction channels (penstocks) that conduct water from reservoirs to turbines, which are located kilometres from the dam, is becoming common, optimizing the electricity generation in small dams. This design creates a river stretch with reduced discharge between the dam and the powerhouse. This study evaluates the short‐term impacts of the below‐dam decrease in river flow on fish assemblages. Samples were collected in the reduced flow stretch of the Castro Alves Hydropower Plant (Antas River, Rio Grande do Sul, Brazil) before the reservoir started operating (January 2008; mean discharge of 103.7 m 3 /s) and immediately after operation began (March 2008; mean discharge of 12.4 m 3 /s). Sampling was conducted in distinct habitats of the reduced flow stretch (slow waters—gillnets, sand beaches—seining nets, structured littoral—electrofishing, and fast waters—cast nets) with a strongly standardized effort. The attributes of the fish assemblages were not negatively affected by the flow reduction in any habitat sampled. However, distinct changes in the spatial structure were observed considering the different types of habitat predominantly used by the species, which represents an entire reorganization of the fish assemblages in the short term. It is fundamental that these short‐term aspects be considered in the licensing of hydropower plants in addition to the long‐term changes.